IMPLEMENTASI SISTEM PERLINTASAN KEIMIGRASIAN MELALUI AUTOGATE DAN KONTER DI TEMPAT PEMERIKSAAN IMIGRASI (TPI) SOEKARNO-HATTA - wilonotomo wilonotomo wilonotomo (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2020)
This study aims to answer empirically one of the biggest challenges faced by immigration in terms of implementing a crossing system, especially related to information technology implemented by the Directorate General of Immigration. The theme chosen is the implementation of the crossing system that has been implemented through autogate technology and the classical implementation of the crossing system. The discussion of this theme is the imbalance in the number of users between the two implementations of the system where the application of this crossing system technology should be able to solve queuing problems and also increase effectiveness and efficiency. This analysis uses descriptive analysis by assessing data and information obtained from various sources. The method used is to describe systematically through the research flow that is researched in a precise, simple and easy to do by conducting a theoretical study to deepen the immigration crossing system. The results of this study are in the form of recommendations that aim to provide a description, explanation, and validation of a phenomenon being studied about immigration crossings.